Using Differentiated Instruction to Promote Creativity, Critical Thinking and Learning: Perspective of Teachers - Bobi, Comfort Bobi; Ahiavi, Martin Ahiavi (Journal of Education and Practice, 2023)
Purpose: The purpose of this study was to investigate Basic School teachers' perspectives on the use of differentiated instructional approaches to promote creativity, critical thinking skills, cooperative teaching, and learning in the Ho-West District of Ghana. Methodology: A descriptive research design was employed, and a simple random sampling technique was used to select 289 teachers for the study. The data collected were analyzed using the Statistical Package for the Social Sciences (SPSS) to compute descriptive statistics such as mean, standard deviation, and percentages. Findings: The findings of the study indicated that the teachers in the Ho-West district had a good understanding of differentiated instructional strategies and their impact on student performance. Additionally, the teachers were aware of how differentiated instruction can affect pupils' knowledge and skill acquisition and recognized the importance of learning styles, motivation, and encouragement in improving learning outcomes. Unique Contribution to Theory, Policy and Practice: This study makes a unique contribution to the field of education by providing insights into Basic School teachers' perspectives on the use of differentiated instructional approaches in promoting creativity, critical thinking skills, cooperative teaching, and learning in the Ho-West District of Ghana. The study's findings highlight the need for in-service programs, workshops, seminars, and short courses on differentiated instructional strategies to enhance teachers' practical training and further develop their existing knowledge of differentiated instruction. These findings have significant implications for theory, policy, and practice in education, particularly in the Ho-West District of Ghana. The study recommends that the Ho-West District directorate of the Ghana Education Service and stakeholders in education should organize such programs to enhance teachers' ability to apply differentiated instructional strategies and enhance creativity, critical thinking skills, and cooperative teaching and learning among pupils in the district.